Frequency of hyperkalemia during optimization of guideline-directed medical therapy in ambulatory patients with HFrEF - Genaro H. Mendoza-Zavala; Gibran Reynoso-Hernandez; Edith L. Posada-Martinez; Miguel Sandoval-Jimenez; Jairo I. A. Alejo-Arcos; Kassandra Rios-Felix; Eileen Amaro-Balderas; Marisol Gomez-Lopez; Sonia C. Juarez-Comboni; Luis F. Tejado-Gallegos; Emerson Joachin-Sanchez; Luis Olmos-Dominguez; et al. (Frontiers in Cardiovascular Medicine)
BackgroundThe frequency of hyperkalemia in patients with heart failure with reduced ejection fraction (HFrEF) receiving a high percentage of quadruple guideline-directed medical therapy (GDMT) has not been described extensively. The consequences of hyperkalemia on modifications in GDMT have not been fully addressed in patients receiving quadruple therapy.MethodsThis was a retrospective cohort study of outpatients with HFrEF treated at a specialized heart failure clinic. A case-by-case retrospective review of patients fulfilling the selection criteria was conducted by dedicated personnel. The main exposure was the occurrence of hyperkalemia at any visit, and the primary outcome was the modification in GDMT following hyperkalemia.ResultsWe included 1,279 medical encounters from 500 unique patients. Over a mean follow-up of 11 ± 7 months (2.6 ± 0.9 visits), the proportion of patients receiving angiotensin-converting enzyme inhibitor/angiotensin receptor blocker/angiotensin receptor-neprilysin inhibitor, beta-blockers, spironolactone, sodium-glucose co-transporter 2 inhibitors (SGLT2is), and quadruple therapy increased to 98.6%, 99.0%, 97.4%, 93%, and 89.6%, respectively (P < 0.001 compared to baseline). The proportion of hyperkalemia during follow-up, defined as serum potassium >5.0,>5.5, and >6.0 mmol/L at any visit, was 44.4%, 13.0%, and 4.0%, respectively. In multivariable analysis, estimated glomerular filtration rate was the only independent predictor of hyperkalemia across all cutoff values (P < 0.001 for all). Serum potassium was associated with greater odds of mineralocorticoid receptor antagonist (MRA) discontinuation in a non-linear fashion, with an increased risk starting at >5.0 mmol/L (P < 0.001). Initiation of SGLT2is was not associated with lower odds of developing hyperkalemia at subsequent visits (P > 0.20 for all cutoff values).ConclusionsHyperkalemia >5.0 mmol/L is highly prevalent in patients with HFrEF receiving quadruple GDMT. Even with mild hyperkalemia, discontinuation of MRAs remains the primary strategy for managing this complication.